PENGARUH ION KARBONAT DALAM PROSES PRESIPITASI SENYAWA KALSIUM FOSFAT - S, Siti Ahmiatri; Soejoko, Djarwani S (Makara Journal of Science, 2002)
An experiment has been conducted to fi nd out the effect of ion carbonate in the calcium phosphate precipitation process. It was conducted by adding CaCl2 .2H2 O 8 mM into Na2 HPO4 .2H2 O 8 mM and NaHCO3 . The NaHCO3 concentrations varied from 0 mM, 16 mM, 80 mM, 320 mM, and 720 mM. The results of the infra red measurement indicated that the precipitation in the form of carbonate apatite crystals particularly at low ion carbonate concentrations. However, if ion carbonate concentration was higher than 80 mM the crystallization process was disturbed, and the produced calcium phosphate was dominated by amorf phase. Besides this calcium phosphate amorf, calcium carbonate compound that probably also in the form of amorf phase was also produced. Stirring of the solution infl uenced the crystallization process. It was likely that the longer time of stirring would inhibit the crystallization of calcium phosphates, but it enhanced the crystallization of calcium carbonates in the form of calcites